"In these pandemic times": The role of temporal meanings in ambient affiliation about COVID-19 on Twitter. (June 2022) - Zappavigna, Michele; Dreyfus, Shoshana
Highlights: Temporal meanings about the pandemic are found in many tweets. Temporal meanings play an important role in interpersonal meaning. Three key affiliation strategies in the dataset involve temporal meanings. Abstract: This paper explores the role of a particular set of commonly occurring temporal meanings relating to the shared experience of being in a pandemic (e.g.,   in these unprecedented times ) and how these foster ambient affiliation on Twitter. Temporal meanings can be realised as a range of grammatical structures in texts and are linguistic resources that add meaning – in terms of dimensions such as manner, time, or place – to the main activities, entities or events in a clause. While often viewed in terms of their role in how experience is represented, we suggest they play a pivotal interpersonal role in how values are positioned and how social bonds are offered to ambient audiences. The paper also draws on communing affiliation, a system in the ambient affiliation framework for understanding how people share and contest values in social media environments, to show how these temporal meanings are functioning. Corpus-based discourse analysis of the contribution of temporal meanings to communing affiliation in a large of corpus of COVID-19 tweets was undertaken. Three major affiliation strategies that these temporal meanings were involved in were observed: centring in the service of convoking affiliation, contrasting in the service of finessing affiliation, and accentuating in the service of promoting affiliation.